Molecular prevalence of Borrelia burgdorferi, Ehrlichia canis, and Coxiella burnetii in dogs and associated ticks in Egypt: Emerging One Health challenging zoonoses - Zeinab S. Ahmed; Nada Hesham; Taher M. Abdelhamid; Mahmoud E. Hashad; Hossam Mahmoud (Veterinary World)
Background and Aim: Tick-borne pathogens pose a significant problem in canines, other animals, and humans worldwide. This study aimed to estimate the prevalence of Borrelia burgdorferi, Ehrlichia canis, and Coxiella burnetii in dogs and associated ticks in Egypt.